Impact electrochemistry on screen-printed electrodes for the detection of monodispersed silver nanoparticles of sizes 10–107 nm. Issue 40 (3rd October 2016) - Nasir, Muhammad Zafir Mohamad; Pumera, Martin
Abstract : We discuss the use of screen-printed electrodes for the impact electrochemistry detection of well-defined monodispersed silver nanoparticles of sizes 10, 20, 40, 80, and 107 nm. Abstract : Impact electrochemistry provides a useful alternative technique for the detection of silver nanoparticles in solutions. The combined use of impact electrochemistry on screen-printed electrodes (SPEs) for the successful detection of silver nanoparticles provides an avenue for future on-site, point-of-care detection devices to be made for environmental, medicinal and biological uses. Here we discuss the use of screen-printed electrodes for the detection of well-defined monodispersed silver nanoparticles of sizes 10, 20, 40, 80, and 107 nm.